Seasonal variation in blood pressure: Evidence, consensus and recommendations for clinical practice. Consensus statement by the European Society of Hypertension Working Group on Blood Pressure Monitoring and Cardiovascular Variability. Issue 7 (July 2020) - Stergiou, George S.; Palatini, Paolo; Modesti, Pietro A.; Asayama, Kei; Asmar, Roland; Bilo, Grzegorz; de la Sierra, Alejandro; Dolan, Eamon; Head, Geoffrey; Kario, Kazuomi; Kollias, Anastasios; Manios, Efstathios; et al.
Abstract : N/A: Blood pressure (BP) exhibits seasonal variation with lower levels at higher environmental temperatures and higher at lower temperatures. This is a global phenomenon affecting both sexes, all age groups, normotensive individuals, and hypertensive patients. In treated hypertensive patients it may result in excessive BP decline in summer, or rise in winter, possibly deserving treatment modification. This Consensus Statement by the European Society of Hypertension Working Group on BP Monitoring and Cardiovascular Variability provides a review of the evidence on the seasonal BP variation regarding its epidemiology, pathophysiology, relevance, magnitude, and the findings using different measurement methods. Consensus recommendations are provided for health professionals on how to evaluate the seasonal BP changes in treated hypertensive patients and when treatment modification might be justified. (i) In treated hypertensive patients symptoms appearing with temperature rise and suggesting overtreatment must be investigated for possible excessive BP drop due to seasonal variation. On the other hand, a BP rise during cold weather, might be due to seasonal variation. (ii) The seasonal BP changes should be confirmed by repeated office measurements; preferably with home or ambulatory BP monitoring. Other reasons for BP change must be excluded. (iii) Similar issues might appear in people traveling from cold to hot places, or the reverse. (iv) BP levels below the recommended treatment goal should be considered for possible down-titration, particularly if there are symptoms suggesting overtreatment. SBP less than 110 mmHg requires consideration for treatment down-titration, even in asymptomatic patients. Further research is needed on the optimal management of the seasonal BP changes.